Metode Digital Storytelling Pada Pembelajaran IPS Terhadap Hasil Belajar Siswa - Nilam Utama (JURNAL ILMIAH EDUKATIF, 2022)
The purpose of this study is to find out, recognize and understand how the digital storytelling method can improve student learning outcomes in the social studies field. This research uses a qualitative descriptive approach with non-empirical characteristics, which means that the research is carried out through a literature study (literature review). This type of method is used to discuss the effect of digital storytelling on social studies learning on student learning outcomes. This research will later be presented in the form of a Literature Review from the data obtained through journal submissions. From the results obtained the digital storytelling method can be used as an information technology medium that makes it easier for students to analyze a developing social event and can make the learning system more fun. Therefore students are expected to find it easier to effectively solve social problems discussed in social studies learning and improve student learning outcomes.